A identidade do velho na cibercultura: análise cultural da experiência do grupo Os Mais Vividos de Uberlândia - Santos, Sílvia Beatriz dos (2019)
This dissertation aims to evaluate how the old subject, here understood as a marginalized group of society, is able to transpose his life experiences in the establishment of a communicative process with meaning and promotion of knowledge for his life and the relationship with the other. The guiding question of this research is: could somebody affirm that, in a old age, the subject is being able to relate and problematize his life stories and his identity through the communicative use of cyberculture? Therefore, the methodology used in the development of the research will be the cultural analysis as a method of investigation of the communicative processes and based on the centrality of the subject in social practices. From this method, it has sought to carry out the analysis of the cultural, social and political conjuncture in which the old man is inserted, emphasizing the importance of his lived moments, his experiences, his choices and actions practiced throughout his life. In cyberculture, the dynamics of social relations acquires a new body that places the subject in conflict with the structure and before other perspectives. For this reason, sought to understand, throughout the work, if the old man can materialize his knowledge, his memory and his identity within this new real space and at the same time virtual, of new features, unknown and constant transformation.